The Effects of Peers' Beliefs on 8th-Grade Students' Identification With School - Radziwon, Christopher D. (Journal of research in childhood education, 2003)
This study investigated two antecedents of students' identification with school-namely, academic achievement and perceived peer beliefs about school-as mediated by race and gender. Participants included 3,346 eighth-grade students from Tennessee, 74% Caucasian and 26% African American. The Identification With School questionnaire (Voelkl, 1996) and a Peer Beliefs questionnaire, developed for this study, were used to measure the students' identification with school and perceived peer beliefs, respectively. The Comprehensive Tests of Basic Skills (CTBS) were used to measure academic achievement. A stepwise multiple regression was used to examine the impact of the independent variables of race, gender, academic achievement, and perceived peer beliefs on the dependent variable of identification with school. Females had higher levels of identification than males, and African Americans had higher levels of identification than Caucasians. The main finding of the study, however, concerned the hypothesis that perceived peer beliefs are related to identification with school. This hypothesis was supported, with perceived peer beliefs accounting for 27% of the variation in students' identification with school, above and beyond gender, race, and academic achievement, making perceived peer beliefs a stronger predictor of identification with school than academic achievement, gender, race, or any of the interaction possibilities.